Accounting for magnetic saturation in designing a SRM speed controller for torque ripple minimization - Youness Boumaalif; Hamid Ouadi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This study established a nonlinear control design for switched reluctance motor (SRM) vehicle applications, using the backstepping approach. The suggested controller is established according to a model that consider magnetic saturation while reducing torque ripple and resulting in less vibrations. To optimize torque ripple, control angles are adjusted based on the machine speed and torque measurements. Indeed, a lookup table is constructed, offering the efficient control angles for various motor operating points. The suggested control technique was validated through simulation, exploiting an accurate MATLAB SRM model considering magnetic saturation effects. To illustrate the superiority of the suggested regulator, a comparison of its performance with a proportional-integral (PI) controller was performed. The acquired findings indicate the suggested regulator’s effectiveness.